Il vero viaggio non consiste nel cercare nuove terre, ma nell’avere nuovi occhi (Marcel Proust) - Canevese, Erminio Paolo; Benedet, Nicola (GEOmedia, 2013)
Cultural ass ets are a key resource for all countries, given the extraordinary capacity of tourist attractions that are able to exercise. This is true especially for Italy, a country among the richest in terms of artistic heritage.